(untitled) (Brazilian Journal of Police Sciences, 2026)
The present study had the general objective of analyzing the level and effectiveness of electronic monitoring of custodians using ankle bracelets in criminal recidivism. Exploratory research through case study with qualitative and quantitative data on the recidivism of crime among prisoners in flagrante delicto in the region of the 1st Company of the 3rd Battalion. Survey of information on prisoners caught in flagrante delicto for committing a crime with the State Secretariat for Penitentiary Administration - SEAP; analyzed according to descriptive statistics. Electronic monitoring is a method with a low level of effectiveness in terms of reducing criminal recidivism, as research has shown a high number of evasions from the monitoring system, with 30% of those being held in custody in 2022. in the State. Therefore, 57.5% of those caught in the act are repeat offenders; 20% of prisoners caught in the act were being monitored or had broken their ankle bracelets; 56.6% released after custody. The hearing and legislation came with the intention of promoting a reduction in the population in prisons. Monitoring technology needs to be improved along with the processes that permeate this measure.